تعليمية اللغة العربية، الواقع والآفاق: Educational Arabic language, reality and prospects - Al-Sabti, Kehl (SIBAWAYH Arabic Language and Education, 2020)
It’s obvious to everyone than the language plays a very important role in the life of the individual and so it became vert important that we take care of our language since it is the means of communication between the individual and others and so we must develop tools to promote it so that we create such a link the market as well as work, administration, economy and so considering it as being such an important subject as we develop undoubtedly each time we speak.Taking care if one’ is language is considered as a priority to preserve one‘s patrimony, since it lives and dies with its people and diffuses efficiently each time it translates its natives achievements. With which language can we, acquire the other civilazations and different cultures, if our language is in isolation about is happening arand us ?